2003
DOI: 10.1046/j.1538-7836.2003.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in factor VIII concentrate measurement: results from SSC field collaborative studies

Abstract: Summary. Seven 'field' collaborative studies on factor (F)VIII concentrate potency measurements were carried out, using local routine methodology, standards and calculation of results. Data from five of the 12 different concentrates studied are described in detail. These studies revealed that, for the intermediate-purity and the recombinant FVIII concentrates, one-stage potencies were significantly lower than chromogenic potencies, whilst for the two high-purity FVIII concentrates one-stage potencies were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…The potency of FXIII activity in pool N ranged from 87% to 111% (with a lower estimate of 69% from only one laboratory); this variation is hence much less than that observed for some other factors involved in hemostasis and thrombosis, such as a 2-fold range for FVIII [15,18]. The degree of variation in levels of FXIII antigen (A 2 B 2 complex) in the normal plasma pools (pool N) was similarly low as compared to that of the activity levels, ranging from 73% to 116%.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The potency of FXIII activity in pool N ranged from 87% to 111% (with a lower estimate of 69% from only one laboratory); this variation is hence much less than that observed for some other factors involved in hemostasis and thrombosis, such as a 2-fold range for FVIII [15,18]. The degree of variation in levels of FXIII antigen (A 2 B 2 complex) in the normal plasma pools (pool N) was similarly low as compared to that of the activity levels, ranging from 73% to 116%.…”
Section: Discussionmentioning
confidence: 78%
“…These conditions have previously been shown to minimize interlaboratory variability in assays of plasma-derived products [12,14,15]. For the antigen determination in study 2, R-ELISA FXIII kits specific for the A 2 B 2 complex were used by the five SWP laboratories (kindly provided by Reanal, Budapest, Hungary).…”
Section: Assay Methodsmentioning
confidence: 99%
“…The optimal design of cross-over studies to prove the bioequivalence of new recombinant concentrates was defined in terms of samples’ size and timing, outcome variables both by compartmental methods and model-independent analysis, single dose’s amount, and analytical methodology (reference standards, reagents and instrumentation). The well-known variability of FVIII assay [35,36,37,38] had jeopardised the determination of IVR and reliability of post-infusion FVIII/IX concentrations [39]. A European multicentre study aimed to assess the reproducibility of one- and two-stage clotting methods and chromogenic assay of FVIII showed a good agreement between one-stage clotting and chromogenic assay in a wide range of concentrations, while two-stage clotting assay was not well reproducible [40].…”
Section: Dna-recombinant Clotting Factor Concentrates and Their Phmentioning
confidence: 99%
“…The chromogenic assays are generally based on indicators of activated factor X (FXa) enzymatic activity as a measure of FVIII cofactor activity on factor IX (FIX) [8,9]. A variety of studies have demonstrated that using the traditional calibrators, such as that provided by the International Society of Thrombosis and Hemostasis (ISTH), one-stage clotting assays underestimate plasma levels of FVIII by 20-50% when compared with chromogenic and immunological assays in severe haemophilia A patients infused with BDD-rFVIII [10][11][12], FVIII-deficient plasmas containing full-length rFVIII concentrates [13] or BDD-rFVIII [14,15]. This bias has been attributed to differences between BDD-rFVIII and pd-FVIII in either proteolytic inactivation (as inactivation of activated BDD-review is two to three times faster by activated protein C and five to six times faster by FXa [9]) or variability in metabolism and clearance [10].…”
mentioning
confidence: 99%
“…Moreover, the precision of chromogenic assays using predilution and 1% albumin in assay buffers, as recommended by the ISTH/Scientific and Standardization Committee [17], is superior to that of one-stage assays [8,15]. However, the use of chromogenic assays in patients receiving BDD-rFVIII raises some doubts from a clinical perspective, as the two different methodologies appear to reflect two faces of a haemostatic coin.…”
mentioning
confidence: 99%